A Mathematics Course for Political and Social Research - Moore, Will H.; Siegel, David A. (Princeton University Press, 2013)
Political science and sociology increasingly rely on mathematical modeling and sophisticated data analysis, and many graduate programs in these fields now require students to take a "math camp" or a semester-long or yearlong course to acquire the necessary skills. The problem is that most available textbooks are written for mathematics or economics majors, and fail to convey to students of political science and sociology the reasons for learning often-abstract mathematical concepts.A Mathematics Course for Political and Social Researchfills this gap, providing both a primer for math novices and a handy reference for seasoned researchers. The book begins with the fundamental building blocks of mathematics and basic algebra, then goes on to cover essential subjects such as calculus in one and more than one variable, including optimization, constrained optimization, and implicit functions; linear algebra, including Markov chains and eigenvectors; and probability. It describes the intermediate steps most other textbooks leave out, features numerous exercises throughout, and grounds all concepts by illustrating their use and importance in political science and sociology. Uniquely designed for students and researchers in political science and sociology Uses examples from political science and sociology Features "Why Do I Care?" sections that explain why concepts are useful to practicing political scientists and sociologists Includes numerous exercises Complete online solutions manual (available only to professors) Selected solutions available online to students